J-shaped association of dietary catechins intake with the prevalence of osteoarthritis and moderating effect of physical activity: an American population-based cohort study - Fu, Yuesong; Li, Lu; Gao, Jing; Wang, Fazheng; Zhou, Zihan; Zhang, Yiwei (Frontiers in Immunology, 2024)
Background: Catechins are a class of natural compounds with a variety of health benefits, The relationship between catechins and the prevalence of osteoarthritis (OA) is unknown. This study investigated the associations between daily intake of catechins and the prevalence of OA among American adults and assessed the moderating effect of physical activity (PA).Methods: This study included 10,039 participants from the National Health and Nutrition Examination Survey (2007)(2008)(2009)(2010)(2017)(2018). The logistic regression, weighted quantile sum (WQS) regression, and restricted cubic spline (RCS) regression models were conducted to explore the associations between daily intake of catechins and the prevalence of OA. Moreover, interaction tests were performed to assess the moderating effect of PA.Results: After multivariable adjustment, the weighted multivariable logistic regression and RCS regression analyses revealed significant J-shaped non-linear correlations between showed that intakes of epigallocatechin and epigallocatechin 3-gallate had significant associations with the prevalence of OA among in U.S. adults, . WQS regression analysis showed that excessive epigallocatechin intake was the most significant risk factor for OA among all subtypes of catechins.and WQS regression indicated that epigallocatechin intake was the major risk factor among the mixed exposure factors. RCS analysis results showed J-shaped associations between epigallocatechin and epigallocatechin 3-gallate intakes and the prevalence of OA. In the interaction assay, PA showed a significant moderating effect in the relationship between epigallocatechin intake and OA prevalence.The intake of gallocatechin and gallocatechin 3-gallate had a significant negative correlation with the prevalence of OA and the dose-response relationship was J-shaped.Nonlinear associations of intake of Epigallocatechin and Epigallocatechin 3-gallate and prevalence of OA were observed in American patients.PA below 150 MET-min/ weekModerate PA (<150 MET-min/wk) and the threshold intakes of 32.70mg/d for epigallocatechin and 76.24mg/d for epigallocatechin 3-gallate might be the targets for interventions to reduce the risk of developing OA.